Pengaruh Kualitas Layanan terhadap Kepuasan Pengunjung Agrowisata Bali Pulina untuk Membentuk Minat Kunjungan Ulang - PURNAMI, NI NYOMAN ALIT; SURYAWARDANI, IGA. OKA; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.1, Januari 2019DO - 10.24843/JAA.2019.v08.i01.p07, 2019)
Effect of Service Quality on Satisfaction of Visitors of Bali Pulina Agro Tourism Forming their Interest in Repeating Visits Visitors perceptions of the quality of Bali Pulina's agrotourism services will give them satisfaction, which in turn will form the interest of visitors to re-visit. The research was conducted at Bali Pulina agrotourism. This study aims to analyze the effect of service quality (physical evidence, reliability, responsiveness, assurance, and empathy) on visitor satisfaction over Bali Pulina agro tourism and analyze the effect of visitor satisfaction on the interest to re-visit. Respondents in this study were tourists who had visited Bali Pulina agro tourism. The number of sample respondents was 80 respondents obtained based on the accidental sampling method. The model was designed based on the Structural Equation Modeling (SEM) approach based on Smart PLS version 3.0 which was analyzed using a computer program. The results showed that physical evidence had a significant effect on visitor satisfaction (p = 0.002). Reliability had a significant effect on visitor satisfaction (p = 0.005). Capture had a significant effect on visitor satisfaction (p = 0.040). Guarantee had a significant effect on visitor satisfaction (p = 0.001). Empathy had a significant effect on visitor satisfaction (p = 0.014). Visitor satisfaction had a significant effect on interests in repeat visits (p = 0,000). Based on the results of the study, Bali Pulina agrotourism is expected to be able to maintain and improve the quality of services, so that visitors feel satisfied and intend to make a repeat visit.